The turquoise management style is a utopia or the future of modern ("Journal "U". Economy. Management. Finance.", 2023)
This study examines the possibility of applying the turquoise management style at enterprises in modern Russia. What difficulties and positive aspects can both the employer and employees face. Can this management style exist in its pure form and does it have a future.
Keywords: motivation; stimulation; labor stimulation; turquoise management style; management; labor